Exceptional response to Erlotinib monotherapy in EGFR Exon 19-deleted, KRAS wild-type, Chemo-refractory advanced pancreatic adenocarcinoma. (2021) - Park, Robin; Al-Jumayli, Mohammed; Miller, Kirk; Saeed, Azhar; Saeed, Anwaar
Abstract: Advanced pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive tumor with an abysmal prognosis. Beyond the first-line setting, treatment for advanced PDAC is limited and suboptimal. Also, the efficacy of epidermal growth factor receptor (EGFR) targeted therapy alone in the chemo-refractory setting in PDAC tumors harboring druggable EGFR mutations is unclear. Here we describe the case of a patient with chemo-refractory advanced PDAC with an activating exon-19 EGFR mutation who had an exceptional response to erlotinib monotherapy.